In situ preparation of glyco-micromotors and their bacteria loading/guiding ability. Issue 78 (9th September 2022) - Shan, Fangjian; Hu, Jun; Gu, Chuan; Zhou, Yue; Zhang, Zexin; Chen, Gaojian
Abstract : We successfully synthesized glyco-micromotors in situ directed by multifunctional glycopolymers. The fabricated glyco-micromotor presents abilities in loading and guiding bacteria. Abstract : We successfully synthesized glyco-micromotors in situ directed by multifunctional glycopolymers, which were obtained by copolymerizing 2-methacrylamido glucopyranose (MAG) and 2-(diethylamino)ethyl methacrylate (DEAEMA) monomers. The fabricated glyco-micromotors present abilities in loading and guiding bacteria with different individual and group motions.